Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to follow some notes on beam mechanics, and there is a differentiation step I don't understand.

He goes from:

$M_n(\lambda(1-R)+R) = \frac{1}{3} + \frac{(R-1)(1-\lambda)^2(2+\lambda)}{6}$

to:

$\frac{dM_n}{d\lambda}(\lambda(1-R)+R) + M_n(1-R) = \frac{R-1}{6}(-2(1-\lambda)(2+\lambda)+(1-\lambda)^2)$

I can do the R.H.S, but I don't understand how the L.H.S is differentiated. Also some insights into how the R.H.S is differentiated in one step would be very useful!

Can anyone help me understand this please?

Thanks.

share|improve this question
add comment

1 Answer

up vote 1 down vote accepted

Consider the lhs as a product of two functions $f(\lambda) = M_n (\lambda)$ and $g(\lambda) = \lambda(1-R) +R$.

Note that $f'(\lambda) = \frac{dM_n}{d\lambda}$, $g'(\lambda) = 1-R$.

Then the derivative wrt $\lambda$ is:

$$f'(\lambda)g(\lambda)+f(\lambda)g'(\lambda)= \frac{dM_n}{d\lambda}(\lambda(1-R) +R)+M_n (\lambda)(1-R).$$

share|improve this answer
    
Ah of course, thank you. It's been a long time since I've done any of this. You've got a slight typo though the (1+R) terms should be (1-R) –  Griffin Jun 2 '12 at 16:22
    
Any idea how the R.H.S is done in one step, btw? –  Griffin Jun 2 '12 at 16:24
1  
I am not sure what you mean by one step. It is another application of the product rule applied to $(1-\lambda)^2(2+\lambda)$. –  copper.hat Jun 2 '12 at 16:41
    
Wow I feel like an idiot, I multiplied out the brackets!. Thank you very much. –  Griffin Jun 2 '12 at 16:55
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.